Comparison of the levels of marital adjustment of the participants in the Couples of Christ marriage enrichment program and marriage encounter program - Nathan, Edmond Thivia (Animo Repository, 1989)
The study investigates the levels of Marital Adjustment of the participants in the Couples for Christ, Marriage Enrichment program and those who have participated in the marriage encounter program. The study was viewed from the pastoral, scriptual and psychological points of view. Marital adjustment identified along thirteen areas of married life were marital satisfaction, personality traits, openness in communication, conflict resolution, handling financial concern, leisure activities, sexual relationship, parenting children, family and friends, egalitarian roles, religious orientation, marital cohesion and marital adaptability. The following hypothesis were presented: 1. There is a significant difference in the level of marital adjustment of the wives who have attended the Couples for Christ program and of those who have attended the Marriage Encounter program. 2. There is a significant difference in the level of marital adjustment of husbands who have attended the Couples for Christ program and of those who have not attended the Marriage Encounter program 3. There is a significant difference in the levels of Marital Adjustment of the couples who have participated in the Couples for Christ program and of those who have participated in the Marriage Encounter in terms of the thirteen areas of married life. The study utilized the descriptive comparative research design using the survey technique, and data were collected by the use of the Enrich (Evaluation and Nurturing Relationship, Issues Communication and Happiness) questionnaire. The number of respondents were 50 randomly chosen couples, from each group. They come from different parts of Metro Manila. The statistical treatment used was the t-test for independent samples. The results showed a significant difference in the levels of marital adjustment between wives of Couples for Christ and the wives of the Marriage Encounter programs. However, there was no significant difference between husbands in both groups. Lastly, there was a significant difference in the levels of marital adjustment such as personality traits, communication, parenting children and religious orientation between the couples of the two groups. The results showed that both enrichment programs are helpful to bring about marital adjustment or enrichment. Some suggestions for future studies are: Further study is recommended on a larger sample. A follow up study on the respondents of Couples for Christ program and Marriage Encounter program is recommended. Religious dimension and Communication skills can be combined to bring a higher level of marital adjustment. In future studies, the questionnaire can be improved by adding such as in-law relationship, and temporary separation of spouses.